Aging Properties and Mechanism of Microwave-Activated Crumb Rubber Modified Asphalt Binder - Zhou, Tao; Zhou, Jianing; Li, Qidong; Li, Bo (Frontiers in Materials, 2020)
Although crumb rubber modified asphalt (CRMA) has better pavement performance than matrix asphalt (MA), the application bottlenecks of this material in road engineeringlies is its high viscosity, poor workability and bad storage stability. Microwave technology can activate crumb rubber and improve their compatibility. This study investigates the changes in the physical and chemical properties of microwave-activated crumb rubber modified asphalt (MACRMA) under short-term aging and long-term aging conditions, as well as the microscopic mechanism of aging. Through penetration, softening point, ductility and viscosity tests, the high and low temperature performance and temperature sensitivity of MA, CRMA and MACRMA before and after aging were studied. Use gel permeation chromatography (GPC) test to determine the molecular weight distribution of three kinds of asphalt during the experiment. The fourier transform infrared spectroscopy (FTIR) test was used to measure the functional group changes of each asphalt. The results shown that the aging resistance of MACRMA, compared with MA and CRMA, has been significantly improved. The GPC test found that the aging effect aggregated the small molecular chains to large molecular chains in asphalt, and the values of large molecular size (LMS) increased with the aging effect continuing. The LMS value has a high correlation with test indicators, among which the correlation with viscosity is as high as 0.998. Therefore, LMS is a good index to quantitatively characterize the change of MACRMA performance before and after aging. FTIR test found that the carbonyl and sulfoxide functional group indices of MACRMA were lower than those of MA and CRMA, which further confirmed the excellent anti-aging performance of MACRMA.